National and Universal in the Education System. The Process of Globalization and Transformations of Educational Systems - Hovhannisyan, Hovhannes (Տիգրան Մեծ)
In the education system of any nation, there are, to one degree or another, both universal and local, national tendencies and patterns. It can also be noted that it is in national schools that, in the terminology of synergetic, those dissipative structures of educational technologies and methods of organizing education are formed and polished, which are subsequently mastered by other nations and countries, spread and standardized as the most productive means. The article emphasizes the importance of implementing globalization processes not in opposition to or at the expense of national education systems, but in the spirit of their harmonious, mutual enrichment and influence.
Keywords: Education system